Tinjauan Hukum Terhadap Implementasi Employee branding dalam Strategi Pemasaran Perusahaan di Indonesia - Susanto, Asmara Nova; AmbarwatiAmbarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this journal is to analyze the legal perspective on the implementation of employee branding in the marketing strategy of companies in Indonesia. Employee branding aims to build a company's image through the active role of employees, but has not been specifically regulated in existing regulations. An unbalanced branding policy can cause conflicts, such as violations of privacy, freedom of expression, and the right to fair treatment. The method of writing this journal uses a normative legal approach. The results of the study show that there are no specific regulations governing this strategy, so companies rely on internal policies, employment contracts, and Collective Labor Agreements (PKB) to determine branding obligations. However, an unproportional branding policy can cause conflicts, such as violations of the right to privacy, freedom of expression, and fair treatment.